2023
DOI: 10.5802/crgeos.176
|View full text |Cite
|
Sign up to set email alerts
|

Ground deformation monitoring of the eruption offshore Mayotte

Abstract: Ground deformation monitoring of the eruption offshore MayotteSuivi des déformations liées à l'éruption au large de Mayotte

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This 820 m tall, 5.0 ± 0.3 km 3 volcanic edifice, now officially called "Fani Maoré", built in one year of eruption [Rinnert et al, 2019, is interpreted as evidence of the damping of a deep and exceptionally large reservoir. This is supported by the large GPS surface displacements, implying a barycenter of deformation located 40 km eastward of Mayotte and 30 km deep [Lemoine et al, 2020a; see also Peltier et al, 2022].…”
Section: The Recent Mayotte Seismo-volcanic Sequencementioning
confidence: 71%
“…This 820 m tall, 5.0 ± 0.3 km 3 volcanic edifice, now officially called "Fani Maoré", built in one year of eruption [Rinnert et al, 2019, is interpreted as evidence of the damping of a deep and exceptionally large reservoir. This is supported by the large GPS surface displacements, implying a barycenter of deformation located 40 km eastward of Mayotte and 30 km deep [Lemoine et al, 2020a; see also Peltier et al, 2022].…”
Section: The Recent Mayotte Seismo-volcanic Sequencementioning
confidence: 71%
“…Very-long-period seismic signals were also detected [Cesca et al, 2020, Lemoine et al, 2020, and could be generated by the resonance of a fluid-filled cavity [Feuillet et al, 2021. At the same time, GNSS stations recorded significant ground deformation of the island, with ∼20 cm of subsidence, and a horizontal displacement of ∼15 cm eastward [Lemoine et al, 2020, REVOSIMA, 2022, Peltier et al, 2022. It was later proposed that the intense seismicity and significant surface deformation were linked to the drainage of a deep magma reservoir through dykes, leading to a deep submarine eruption [Cesca et al, 2020, Lemoine et al, 2020.…”
Section: Geological Settingmentioning
confidence: 96%
“…If we now consider that the impulsive events date the emplacement of the lava and that they occurred in the 41 days between the first and last swarms, the effusion rate can be estimated to 14 m 3 /s. Using continuous GNSS data, Peltier et al [33] had estimated the effusion rate by modeling the observed surface deformation and the associated volume variation over time. They computed that the source flow rate decreased from 357 ± 60 m 3 /s in December 2018 to 5 ± 7 m 3 /s in 2021.…”
Section: Evolution In Space and Time Of The Lava Flowsmentioning
confidence: 99%
“…Associated with an important tilt (10-19 cm of subsidence and 21-25 cm eastward displacement) [29,30], this seismicity has been linked with intense magmatic activity at depth, which later gave birth to a new underwater volcanic edifice ∼50 km offshore, named Fani Maoré (Figure 1). Comprehensive seismic catalogs [31,32], ground deformation studies [33], and extensive petrological and geochemical analyses [34,35] have helped interpreting the eruption processes of Fani Maoré as well as previous submarine eruptions in the region. Moreover, several lava flows around the new volcanic structure have been evidenced by repeated bathymetric surveys every 6 months to a year.…”
Section: Introductionmentioning
confidence: 99%